Chemical Study of Mucilage Obtained from Medicinal Plant Cassia rengifera - Singh, P.K.; Singh, Prashant; Singh, Priyanka; Hasan Ali, Kasim (Asian Journal of Chemistry, 2010)
A water-soluble and non-ionic D-galactomannan has been isolated from the seeds of C. rengifera of Indian origin, containing D-galactose and D-mannose in 3:7 molar ratio. Acid catalyzed fragmentation, periodate oxidation, methylation and enzymic hydrolysis showed that the mucilage has a branched structure consisting of a linear chain of β-D-(1→4) linked mannopyranosy units, some of which are substituted at 1→6 by α-D-galactopyranosyl units, glycosidically. This galactomannan have similarity with ghee guar plants.